2019
DOI: 10.31883/pjfns/108526
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Botanical Origin of Honeys with Chemometric Analysis According to Their Antioxidant and Physicochemical Properties

Abstract: The aim of this study was to develop models based on Linear Discriminant Analysis (LDA), Classi cation and Regression Trees (C&RT), and Arti cial Neural Network (ANN) for the prediction of the botanical origin of honeys using their physicochemical parameters as well as their antioxidative and thermal properties. Also Principal Component Analysis (PCA) and Cluster Analysis (CA) were performed as initial steps of data mining. The datasets consisted of 72 honey samples (false acacia, rape, buckwheat, honeydew, li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 43 publications
0
23
0
Order By: Relevance
“…The b* parameter ranged from 8.18 to 12.67 for meadow honey and from 6.84 to 20.00 for black locust honey. In another study, Kaczmarek et al [ 160 ] reported similar results for the color parameter of black locust, buckwheat, rapeseed, and multifloral honey. For black locust honey, the color parameter reported was L* = 51 ± 5.6, a* = −3.41 ± 0.44, b* = 18.6 ± 4.59, H = −0.19 ± 0.05, and C = 18.9 ± 4.49.…”
Section: Resultsmentioning
confidence: 62%
“…The b* parameter ranged from 8.18 to 12.67 for meadow honey and from 6.84 to 20.00 for black locust honey. In another study, Kaczmarek et al [ 160 ] reported similar results for the color parameter of black locust, buckwheat, rapeseed, and multifloral honey. For black locust honey, the color parameter reported was L* = 51 ± 5.6, a* = −3.41 ± 0.44, b* = 18.6 ± 4.59, H = −0.19 ± 0.05, and C = 18.9 ± 4.49.…”
Section: Resultsmentioning
confidence: 62%
“…Multivariate analysis (e.g., principal component analysis-PCA; hierarchical cluster analysis-HCA; linear discriminate analysis-LDA, and others) has very often been used to evaluate and/or classify honeys in terms of their chemical composition or their physicochemical or biological properties. Numerous papers have confirmed the suitability of this method for honey, used either alone [ 10 , 11 , 12 , 13 , 14 ] or in combination with spectroscopic techniques [ 15 ].…”
Section: Introductionmentioning
confidence: 97%
“…[10][11][12]. The combination of the multi-component analysis and chemometric techniques is also increasingly used [13][14][15][16][17][18][19][20]. However, due to the fact that the filtration process affects the chemical composition of honey, it is almost impossible to use all of these methods to properly identify the botanical origin of filtered honeys.…”
Section: Introductionmentioning
confidence: 99%